Analisis Peningkatan Kualitas Laporan Keuangan Melalui SIMDA-NG FMIS Pada Inspektorat Daerah Kota Tegal - Siti Fatimah; Vina Nur Azizah; Ahmad Dhia Iqbal; Gunawan Aji (Akuntansi, 2024)
The aim of this research is to analyze how the use of the SIMDA FMIS application in the Regional Inspectorate of Tegal City can improve the quality of financial reports. Descriptive qualitative research is a type. Primary and secondary data are the types of data used. Interviews, documentation and observations were used to collect data. The research results show that the Regional Inspectorate of Tegal City has used SIMDA FMIS well, according to four indicators: communication, resources, disposition or attitude, and bureaucratic structure. Communication indicators show that communication has gone well, there is no conflict between policy implementers and policy makers and no information distortion, according to communication indicators. Resource indicators are well implemented, there are three factors that ensure the successful use of SIMDA-NG FMIS: resources have adequate expertise and skills; employees are involved in training and education; and facilities and infrastructure that support the use of SIMDA-NG FMIS. Disposition indicators (attitudes), implementers have a positive attitude towards the policy of using the SIMDA-NG FMIS application because it allows employees to prepare financial reports and provide supporting evidence that is more comprehensive, effective and in accordance with the needs for monitoring financial position and performance achievements. Indicators of the bureaucratic structure, especially the level of supervision, have worked well as shown by the smooth submission of financial reports which have never been hampered by SIMDA-NG FMIS.